Implementasi Peraturan Walikota Medan Nomor 21 Tahun 2019 Tentang.Tambahan.Penghasilan Pegawai Aparatur Sipil Negara Dikantor Camat Medan Tembung Kota Medan - Lubis, Nurul Afifah; Kusmanto, Heri; muda, Indra (Universitas Medan Area, 2024)
The aim of this research is to find out how to implement Medan Mayor Regulation Number 21 of 2019 concerning Additional Income for ASN at the Medan Tembung Subdistrict Office, Medan City. This research used qualitative methods with informants consisting of the Head of Financial Administration Subdivision, Head of General Administration Subdivision, and Civil Servants at the Medan Tembung Subdistrict Office, Medan City. Data was collected based on data collection techniques, namely observation, interviews, documentation and data triangulation. The research results show that implementation has gone well, as evidenced by the provision of additional employee income. However, the monitoring mechanism is not yet optimal, and the monitoring and evaluation part is hampered by system constraints, so that transparency in assessing the provision of additional income at the Medan Tembung Subdistrict Office is not yet optimal.